2021
DOI: 10.1136/jitc-2021-sitc2021.071
|View full text |Cite
|
Sign up to set email alerts
|

71 Tumors with higher heterogeneity were associated with superior survival outcome amongst stage I lung cancer patients with low tumor mutational burden (TMB)

Abstract: BackgroundTumor mutational burden (TMB) has been shown to predict response to immune checkpoint inhibitors.1 Furthermore, the FDA has approved the use of TMB as a biomarker for response to pembrolizumab in solid tumors.2 Simultaneously, the relationship between tumor heterogeneity and outcome has been studied across a range of cancer indications and has shown predictive value.3 For Lung Squamous Cell Carcinoma (LUSC) the utility of heterogeneity metrics has not been established. To study this relationship we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…( 21 ) compiled the survival indicators of 103,078 patients with different cancers and included 45 immune-related studies; they finally found that TMB-H (high tumor mutational burden) patients achieved better survival after receiving immunotherapy. In 2020, the Food and Drug Administration (FDA) for first time approved TMB to be used as a diagnostic marker for pan-cancer immunotherapy when unresectability or metastasis occurs ( 22 ). In general, TMB-H has predictive and prognostic potential for the immunotherapy of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…( 21 ) compiled the survival indicators of 103,078 patients with different cancers and included 45 immune-related studies; they finally found that TMB-H (high tumor mutational burden) patients achieved better survival after receiving immunotherapy. In 2020, the Food and Drug Administration (FDA) for first time approved TMB to be used as a diagnostic marker for pan-cancer immunotherapy when unresectability or metastasis occurs ( 22 ). In general, TMB-H has predictive and prognostic potential for the immunotherapy of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al (21) compiled the survival indicators of 103,078 patients with different cancers and included 45 immune-related studies; they finally found that TMB-H (high tumor mutational burden) patients achieved better survival after receiving immunotherapy. In 2020, the Food and Drug Administration (FDA) for first time approved TMB to be used as a diagnostic marker for pan-cancer immunotherapy when unresectability or metastasis occurs (22). In general, TMB-H has predictive and prognostic potential for the immunotherapy of solid tumors.…”
Section: Introductionmentioning
confidence: 99%